Solve the equation. Show your work. 8x – 12 = 4x + 24 8x – 12 = 4x + 24 -4 -4x 4x -12 =+ 24 +12 12 4x 36 4x/4 36/4= 9

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Solve the equation. Show your work. 8x – 12 = 4x + 24 8x – 12 = 4x + 24 -4 -4x 4x -12 =+ 24 +12 12 4x 36 4x/4 36/4= 9

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

Simplifying 8x + -12 = 4x + 24 Reorder the terms: -12 + 8x = 4x + 24 Reorder the terms: -12 + 8x = 24 + 4x Solving -12 + 8x = 24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -12 + 8x + -4x = 24 + 4x + -4x Combine like terms: 8x + -4x = 4x -12 + 4x = 24 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 + 4x = 24 + 0 -12 + 4x = 24 Add '12' to each side of the equation. -12 + 12 + 4x = 24 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 24 + 12 4x = 24 + 12 Combine like terms: 24 + 12 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9 You got it :)
Did i write it right?
Yeah i got what you wrote just not sure if mines is wrong or right.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Because yours is a lot longer seems like i missed something XD
It is correct
Alright thanks Missunshine

Not the answer you are looking for?

Search for more explanations.

Ask your own question